An Easy Synthesis of Monofluorinated Derivatives of Pyrroles from β-Fluoro-β-Nitrostyrenes - Aldoshin, Alexander S. (Molecules, 2021)
The catalyst-free conjugate addition of pyrroles to β-Fluoro-β-nitrostyrenes was investigated. The reaction was found to proceed under solvent-free conditions to form 2-(2-Fluoro-2-nitro-1-arylethyl)-1H-pyrroles. The effectiveness of this approach was demonstrated through the preparation of a series of the target products in a quantitative yield. The kinetics of a conjugate addition of pyrrole was studied in detail to reveal the substituent effect and activation parameters of the reaction. The subsequent base-induced elimination of nitrous acid afforded a series of novel 2-(2-Fluoro-1-arylvinyl)-1H-pyrroles prepared in up to an 85% isolated yield. The two-step sequence herein proposed is an indispensable alternative to a direct reaction with elusive and unstable 1-Fluoroacetylenes.